2021
DOI: 10.1159/000518854
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Dyspnoea as Main Persistent Post-COVID-19 Symptoms in Previously Hospitalized Patients: Related Functional Limitations and Disability

Abstract: <b><i>Background:</i></b> Multicentre studies focussing on specific long-term post-COVID-19 symptoms are scarce. <b><i>Objective:</i></b> The aim of this study was to determine the levels of fatigue and dyspnoea, repercussions on daily life activities, and risk factors associated with fatigue or dyspnoea in COVID-19 survivors at long term after hospital discharge. <b><i>Methods:</i></b> Age, gender, height, weight, symptoms at hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 34 publications
5
88
1
Order By: Relevance
“…The studies which met the inclusion criteria are presented in Tables 2, 3, and 4. A total of 37 studies were included, 23 of which were conducted in Europe, including seven in Italy [14][15][16][17][18][19][20], four in France [21][22][23][24], three in Norway [25][26][27], two in Spain [28,29], two in Germany [30,31], one in Austria [32], one in Denmark [33], one in the Faroe Islands [34], one in Switzerland [35], and one in the UK [36]. Six studies were conducted in China [37][38][39][40][41][42], five in the United States (US) [43][44][45][46][47], two in Iran [48,49], and one in Turkey [50].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies which met the inclusion criteria are presented in Tables 2, 3, and 4. A total of 37 studies were included, 23 of which were conducted in Europe, including seven in Italy [14][15][16][17][18][19][20], four in France [21][22][23][24], three in Norway [25][26][27], two in Spain [28,29], two in Germany [30,31], one in Austria [32], one in Denmark [33], one in the Faroe Islands [34], one in Switzerland [35], and one in the UK [36]. Six studies were conducted in China [37][38][39][40][41][42], five in the United States (US) [43][44][45][46][47], two in Iran [48,49], and one in Turkey [50].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…The majority of the studies were conducted in a hospital setting and most were monocentric. Carvalho-Schneider, 2021 Follow-up of adults with noncritical COVID-19 two months after symptom onset [22] Garrigues, 2020 Post-discharge persistent symptoms and health-related quality of life after hospitalization for COVID-19 [23] Nguyen, 2021 Long-term persistence of olfactory and gustatory disorders in COVID-19 patients [24] Ghosn, 2021 Persistent COVID-19 symptoms are highly prevalent 6 months after hospitalization: results from a large prospective cohort [25] Stavem, 2020 Persistent symptoms 1.5-6 months after COVID-19 in non-hospitalized subjects: a population-based cohort study [26] Soraas, 2021 Self-reported Memory Problems Eight Months after Non-Hospitalized COVID-19 in a Large Cohort [27] Blomberg, 2021 Long COVID affects home-isolated young patients [28] Rosales-Castillo Persistent symptoms after acute COVID-19 infection: importance of follow-up [29] Fernández-de-Las- Sonnweber, 2021 Cardiopulmonary recovery after COVID-19: an observational prospective multicentre trial [33] Bliddal, 2021 Acute and persistent symptoms in non-hospitalized PCR-confirmed COVID-19 patients [34] Petersen, 2020 Long COVID in the Faroe Islands-a longitudinal study among non-hospitalized patients [35] Nehme, 2020 COVID-19 Symptoms: Longitudinal Evolution and Persistence in Outpatient Settings [36] Halpin, 2021 Postdischarge symptoms and rehabilitation needs in survivors of COVID-19 infection: A cross-sectional evaluation [37] Zhao, 2020 Follow-up study of the pulmonary function and related physiological characteristics of COVID-19 survivors three months after recovery [38] Liang, 2020 Three-month Follow-up Study of Survivors of Coronavirus Disease 2019 after Discharge [39] Weng, 2021 Gastrointestinal sequelae 90 days after discharge for COVID-19 [40] Xiong, 2021 Clinical sequelae of COVID-19 survivors in Wuhan, China: a single-centre longitudinal study [41] Huang C, 2021 6-month consequences of COVID-19 in patients discharged from hospital: a cohort study [42] Huang D, 2020 Long-term outcomes and sequelae for 464 COVID-19 patients dischared from Leishan hospital in Wuhan, China [43] Jacobs, 2020 Persistence of symptoms and quality of life at 35 days after hospitalization for COVID- Chopra, 2020 Sixty-Day Outcomes Among Patients Hospitalized With COVID-19 [46] Cellai, 2020 Characterization of prolonged COVID-19 symptoms in an outpatient telemedicine clinic [47] Graham, 2021 Persistent neurologic symptoms and cognitive dysfunction in non-hospitalized Covid-19...…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatigue was present in 61% patients, dyspnea with activity in 55%, and dyspnea at rest in 23.5%. Only 31.1% patient did not exhibit fatigue and/or dyspnea 7 months after hospitalization [13]. The patient in this case report, after 1 year of discharge from the hospital, still felt fatigue and shortness of breath with or without activity, but unfortunately, pulmonary function tests were not performed.…”
Section: Discussionmentioning
confidence: 62%